Design of ultra wideband microstrip patch antenna with band notched characteristics - Hassan, Mahfuz Md Mahmudul (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Fifth generation cellular technology (5G) forums in ASEAN countries has been proposed lower frequency bands for 5G applications at 4.5 – 5.5 GHz and also the fixed-satellite service (FSS) is using 3.3 – 3.8 GHz for C-band. In this project, a single band notched (SBN), a double band notched (DBN) and two variable band notched (VBN) antennas are designed, simulated, fabricated and tested to create notched bands for 5G lower band from 4.5 GHz to 5.5 GHz (1 GHz), C-band 3.3 GHz to 4.2 GHz, (0.9 GHz) and Wi-MAX 3.2 GHz to 3.8 GHz (0.6 GHz) applications in UWB spectrum. Two types of UWB antenna have been designed and proposed by using low cost substrate FR-4 with partial grounding on rectangular patch and tuning fork shaped patch antenna. A single band and dual band notched UWB antennas were designed for 5G lower band by using a slot at the top of the radiating patch and by adding an arc shape open loop (ASOL) on UWB antenna. Two variable band notched UWB antennas were also designed by introducing a semi-circular slot (SCS) on the upper part and by inserting ring shape slits (RSS) in ground plane of UWB respectively. Simulated return losses, patterns, radiation efficiencies, directivities and gains are correlation and compared with available similar antennas and found good agreement. The peak radiation efficiency of 90% and maximum gain of 8.0 dBi are achieved with as low as 28% efficiency and -2.0 dBi gain in rejection bands. All antennas are fabricated using FR-4 substrate and tested using Vector Network Analyzer (VNA). The voltage standing wave ratio (VSWR) and return loss of test results prove that all antennas have excellent performance in notched band and UWB band frequencies by showing good agreement with simulation results, except the measured return loss is slightly different from the simulated result in the notched bandwidth in dual band notched and poor performance from 6 GHz – 8 GHz of UWB in variable band notch antenna. Therefore, designed single notch, dual notch and variable notch ultra-wideband antennas are proposed as a good candidate for 5G lower bands, C-bands and Wi-MAX bands notched applications environment.